2017
DOI: 10.1016/j.ajo.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Crossover Trial Comparing the Impact of Sham or Intranasal Tear Neurostimulation on Conjunctival Goblet Cell Degranulation

Abstract: Purpose The aim of the study was to investigate the effects of the Oculeve Intranasal Lacrimal Neurostimulator (ILN) on conjunctival goblet cell degranulation. Design A randomized, double-masked, placebo-controlled crossover trial Methods A total of 15 subjects (5 normal and 10 dry eye) were enrolled in a three-visit study consisting of one screening and two separate randomized-masked ILN treatments (sham extranasal or intranasal). Tear meniscus height (TMH) was measured by AS-OCT before and after applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Further studies of the TrueTear device confirmed its efficacy for the treatment of DED using additional parameters, including tear meniscus height, degranulation of conjunctival goblet cells, and their area. [19][20][21][22][23][24][25][26][27] The effects of the ITN device on corneal staining as well as the protein and lipid component of tears differ across various studies, 8,20,22,[24][25][26][27] warranting further investigation. Despite its efficacy and safety for the treatment of DED, the ITN device requires deep insertion into the nose, which makes it not practical or comfortable for many patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies of the TrueTear device confirmed its efficacy for the treatment of DED using additional parameters, including tear meniscus height, degranulation of conjunctival goblet cells, and their area. [19][20][21][22][23][24][25][26][27] The effects of the ITN device on corneal staining as well as the protein and lipid component of tears differ across various studies, 8,20,22,[24][25][26][27] warranting further investigation. Despite its efficacy and safety for the treatment of DED, the ITN device requires deep insertion into the nose, which makes it not practical or comfortable for many patients.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to the treatment of DED focuses on increasing tear production by incorporation of an electrical stimulator into a contact lens. This concept is based on a similar intranasal stimulator technology (TrueTear, Allergan, CA, USA) which delivers an intranasal electrical stimulus to stimulate tearing [151] and promote goblet cell secretion [152]. A recent patent highlighted the potential for this type of technology to be manufactured in the form of a contact lens [153].…”
Section: Lacrimal Gland Stimulationmentioning
confidence: 99%
“…Gumus et al . investigated the effects of the Allergan Intranasal Tear Neurostimulator (ITN) on conjunctival goblet cell function in a 15-participant (5 normal and 10 dry eyes), study ( 134 ). IC samples were taken at baseline and after each treatment: right eye samples were used for PAS staining and left eye samples were used for MUC5AC mucin immunostaining.…”
Section: Conjunctivamentioning
confidence: 99%